17 Alpha-hydroxyprogesterone caproate use in a rural state. (12th December 2022) - Ghahremani, Taylor; Phillips, Amy; Magann, Everett F.; McCoy, Hannah; Whittington, Julie; Ounpraseuth, Songthip; Eswaran, Hari
Abstract: Background: 17 alpha-hydroxyprogesterone caproate (17OHP) is used to reduce the recurrent risk of preterm delivery in women with a history of preterm delivery. Meis et al. conducted a double-blind placebo controlled trial to evaluate the effectiveness of 17OHP and observed a significant reduction in the risk of recurrent preterm delivery. The FDA granted 17OHP a conditional approval on 2011. A second study observed that 17OHP did not decrease the risk of a recurrent preterm delivery. Criticism of the second study derived from a dissimilarity of the study population. Objective: Our investigation examined the effectiveness of 17OHP in women with a prior preterm delivery in a rural US state with a patient population similar to the original Meis trial. Study design: 17OHP became largely unavailable (due to cost and local pharmacies no longer compounding 17 OHP) and the University of Arkansas for Medical Sciences, Department of Health, and Arkansas Medicaid co-operated to make 17OHP available to women with a prior PTB in our state. This study was a retrospective review of the 17OHP that was offered to women with a prior preterm delivery. For our retrospective review, logistic regression was used on cases of prior preterm delivery between January 2014 and December of 2018 to examine the relationship between 17OHP injections and preterm delivery. Results: A total of 268 women were analyzed for this review. They were divided into three groups: 0 injections, 1–10 injections, and > 10 injections. We found no relationship between 17OHP injections with preterm delivery. Conclusion: Although our patient population was similar to that of the original Meis trial, our results were more similar to the second study by Blackwell.